(untitled) (LACCEI, 2024)
The present study aims to determine the relationship between sustainability and fair trade in a company in a dairy producing company, 2022 a basic investigation of a quantitative non-experimental cross-sectional approach was carried out, of a descriptive correlational type, the population and sample consisted of 20 providers. The technique used in the study was the survey, likewise, the questionnaire was applied as an instrument. Finally, it was demonstrated that there is a considerable positive relationship between the variable of sustainability and fair trade in the company, These results were verified through the Rho Spearman coefficient, obtaining a correlation of 0.542* a significance level of 0.013, this being less than 0.05, that is to say that the variables are related to each other, demonstrating that sustainability and its dimensions are effectively related to fair trade because they go hand in hand, trade will achieve inclusive development , fair and sustainable, through the promotion of production patterns and alternative and supportive consumption which proposes sustainability.